Inventory Management and Service Delivery in Government Hospitals: A Case Study of Kabale Regional Referral Hospital. - Muhindo, Patience (Kabale University, 2023)
The study aimed at establishing the effect of Inventory management on service delivery in government hospitals using Kabale Regional Referral Hospital (KRRH) as a case study. The research employed a correlational research design to enable the researcher establish the relationship between study variables. The researcher also used mixed methods approach in which qualitative data was used to triangulate quantitative data. Out of the targeted 97 staff, 86 of them were interviewed which resulted into an 89% response rate. The findings revealed that service delivery at KRRH was lacking with majority (63%) of the interviewed staff saying that the patients’ level of satisfaction in regards to the health services offered was generally low and also majority (65%) of them said the health services were not readily available. The chi square test of association revealed that there exists a significant relationship between Service Delivery and Inventory Turnover which implied that inventory management and service delivery in government hospitals were related. The major Inventory Management Techniques that were found out to be used at KRRH were Bulk shipment and ABC Inventory Management. The other techniques that were being used included: Economic Order Quantity (EOQ); Last in First Out (LIFO); First Expire First Out (FEFO); and First In First Out (FIFO) among others. The major challenges that KRRH was facing in IM processes included: Late delivery by the suppliers; Inadequate tools and equipment to use in inventory management like computer software; Manual documentation; Inconsistent tracking of ordered goods and services; Lack of collaboration between the Procurement and Inventory department and other departments; Poor inventory management process; Lack of Transparency amongst the store staff: and Entrance of unauthorized personnel among others. Based on the study findings, the researcher recommended that; efforts should be made by both the government especially the Ministry of Health and development partners to improve the quality of services offered in different healthcare facilities such as recruitment of professional staff and enhancing the storage spaces.